Geochemistry and petrogenesis of Mesoproterozoic mafic granulite and amphibolite dykes from Saltora, Bankura district, Chhotanagpur Gneissic Complex, eastern India: Implications for their emplacement in within-plate setting - Poulami Roy; Bapi Goswami; Ankita Basak; Anwesa Sen; Chittaranjan Bhattacharyya (China Geology)
ABSTRACT: Distinguishing high-grade mafic-ultramafic rocks originally crystallized from within-plate basaltic magmatism is challenging and crucial because the chemical composition of the igneous rocks has been modified during high-grade metamorphism, causing misidentification of the characters of the parental magma. Proterozoic metamorphosed mafic dykes occur throughout the Chhotanagpur Gneissic Complex (CGC) of eastern Indian shield. The E-W trending mafic dykes from the Saltora area in the southeastern CGC underwent metamorphism in two episodes: M1 (650 MPa; 770°C) and M2 (300 MPa; 744°C). The metamafics are enriched in LILE, depleted in HFSE, and display strong fractionation of LREE, nearly flat HREE patterns in a chondrite-normalized REE diagram, and show tholeiitic differentiation trend. Their geochemical affinity is towards rift-related, continental within-plate basalts. About 7%–10% melting of the carbonated spinel-peridotite sub-continental lithospheric mantle (SCLM) produced the parental mafic magma. The pre-existing SCLM was metasomatized by slab-derived fluid during the previous subduction. The upwelling of the asthenosphere in a post-collisional tectonic setting caused E-W trending fractures, lithospheric thinning, and gravitational collapse. These dykes were emplaced during crustal extension around 1070 Ma. The remarkable geochemical similarity between the mafic dykes of Saltora and Dhanbad, the ca. 1096 Ma Mahoba (Bundelkhand craton), and the ca. 1070 Ma Alcurra mafic dykes in Australia supports a genetic link.